CURRICULUM MANAGEMENT IN IMPROVING COMPETITIVE ADVANTAGE IN MADRASAH - Amir (Managere: Indonesian Journal of Educational Management, 2021)
This study aims to find and analyze curriculum management in increasing competitive advantage in Madrasah Aliyah Nurul Jadid, Paiton, Probolinggo, East Java. This study uses a qualitative case study approach. The data collection technique is done through interviews, observation, and documentation. The results showed that curriculum management in increasing competitive advantage at Madrasah Aliyah Nurul Jadid was carried out through; 1) planning, which includes analyzing activities for students, processing material content, analyzing learning techniques or methods, documenting learning components, providing motivation to students; 2) Implementation of the planning design that has been determined together by integrating the government curriculum and pesantren; 3) Evaluation of the implementation of the curriculum, both on the process and its outputs and outcomes, with the principle of continuous improvement.